Towards a theoretical framework for the teaching of religion in state-funded Catholic and other confessional basic schools in Ghana - Ntim, S. (International Studies in Catholic Education, 2012)
This article argues that religion is too pervasive in Ghana to be considered a 'private matter', meant for families and respective faith communities. The paper makes the submission that religion is a double-edged sword. If religion is taught from only one religious perspective with the view to proselytize without exposing students to other religious views, students can become myopic which can be an easy recipe for fanaticism. Based on these assumptions, the paper argues that state-funded Catholic and other confessional basic schools (where the future leadership of the nation is nurtured and bred and where there are other pupils from other confessions) must be engaged in the teaching of religion with the objective to promote religious understanding and tolerance. The paper presents a theoretical framework that will respond to the demands of a secularised state while at the same time respecting divergent religious traditions in a pluralistic society like Ghana. © 2012 Copyright Taylor and Francis Group, LLC.
Keywords: dialogue; education; fanaticism; globalisation; religion